2022
DOI: 10.1097/rlu.0000000000004323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preoperative Imaging Modalities for the Assessment of Malignant Potential of Pancreatic Cystic Lesions

Abstract: The aims of this study are to compare the performance of various preoperative imaging modalities for assessing the malignant potential of pancreatic cystic lesions (PCLs) through a network meta-analysis (NMA) and to clarify the role of 18 F-FDG PET in the management of patients with PCL. Methods: PubMed, EMBASE, and Cochrane Library were searched for the studies evaluating the performance of preoperative imaging modalities for identifying malignant PCLs. The NMA was performed for 4 representative categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…Além disso, há ainda o PET/CT, uma técnica que utiliza a tomografia por emissão de pósitrons (PET) adjunta a tomografía computarizada convencional para diagnosticar e diferenciar tumores primários e detectar metástases (LIU et al, 2023). O PET/CT utilizado com flúor-18-fluorodesoxiglicose (18 F-FDG) é um traçado utilizado para avaliação sistemática pré-operatória que, apesar do seu alto custo, sugere maior modalidade em diferenciação de câncer de pâncreas malígnos e benígnos (LIU et al, 2023;LEE et al, 2022). O F-FDG PET mostrou maior eficiência em questão de sensibilidade e especificidade na diferenciação de câncer de pâncreas maligno e benigno seguido por ressonância magnética ou tomografia computadorizada (LEE et al, 2022).…”
Section: Principais Exames De Imagemunclassified
See 1 more Smart Citation
“…Além disso, há ainda o PET/CT, uma técnica que utiliza a tomografia por emissão de pósitrons (PET) adjunta a tomografía computarizada convencional para diagnosticar e diferenciar tumores primários e detectar metástases (LIU et al, 2023). O PET/CT utilizado com flúor-18-fluorodesoxiglicose (18 F-FDG) é um traçado utilizado para avaliação sistemática pré-operatória que, apesar do seu alto custo, sugere maior modalidade em diferenciação de câncer de pâncreas malígnos e benígnos (LIU et al, 2023;LEE et al, 2022). O F-FDG PET mostrou maior eficiência em questão de sensibilidade e especificidade na diferenciação de câncer de pâncreas maligno e benigno seguido por ressonância magnética ou tomografia computadorizada (LEE et al, 2022).…”
Section: Principais Exames De Imagemunclassified
“…O PET/CT utilizado com flúor-18-fluorodesoxiglicose (18 F-FDG) é um traçado utilizado para avaliação sistemática pré-operatória que, apesar do seu alto custo, sugere maior modalidade em diferenciação de câncer de pâncreas malígnos e benígnos (LIU et al, 2023;LEE et al, 2022). O F-FDG PET mostrou maior eficiência em questão de sensibilidade e especificidade na diferenciação de câncer de pâncreas maligno e benigno seguido por ressonância magnética ou tomografia computadorizada (LEE et al, 2022). A figura 1 apresenta um fluxograma resumindo as características distintivas dos tipos de exames de imagem utilizados para a avaliação do câncer de pâncreas.…”
Section: Principais Exames De Imagemunclassified
“…However, it is important to know that, although 18-FDG PET or PET/CT is noninvasive, without a risk of radiation exposure, 18-FDG is not specific to the tumor cells and has the potential to accumulate in inflammatory cells, resulting in false-positive findings. A network meta-analysis including 1018 patients from 17 direct comparison studies (8 studies used F18-FDG PET or PET/CT) showed that the positive predictive value and accuracy of F18 FDG PET in differentiating malignant from benign PCLs were significantly higher than CT or MRI in all PCLs, including IPMNs [42]. Therefore, F18-FDG PET or PET/CT may complement the Fukuoka guidelines for the preoperative management of PCLs.…”
Section: F-18 Fluorodeoxyglucose (Fdg) Positron Emission Tomography (...mentioning
confidence: 99%
“…Additionally, MRI assessment of cyst fluid together with other signs may predict the malignant transformation of IPMNs [58], assisted by three dimensional (3D)-MRCP [59] or 3T MRI [60]. It has been postulated that 18 F-Fluorodeoxyglucose ( 18 FDG)-PET is the best imaging tool for malignant cystic lesions [61]. A screening system using forward viewing radial EUS and MRI/MRCP for screening individuals with a family history of pancreatic cancer has been proposed [62].…”
Section:  Diagnosismentioning
confidence: 99%